Impact of submarine volcanic versus hydrothermal activity onto the strontium and lithium isotopic signatures of the water column (TONGA) - Chavagnac, Valérie; Destrigneville, Christine; Boulart, Cédric; Taillandier, Vincent; Vigier, Nathalie; Guieu, Cecile; Bonnet, Sophie (Frontiers in Marine Science, 2024)
During the TONGA cruise (2019), seawater samples were collected to assess the effect of volcanic eruption versus submarine hydrothermal system on the water column. For this purpose, two locations were investigated, the first one located directly under the influence of the New Late’iki island (eruption in October 2019), and the second one showing ongoing submarine hydrothermal activity. At both locations, the total strontium (TSr) and lithium (TLi) concentrations vary between 94.4 and 152.3 µmol/L and 13.2 and 203.5 µmol/L, respectively. When combined, TSr and TLi concentrations of all samples in the water column are higher than those of the oligotrophic water. Both volcanic eruption and submarine hydrothermal activity (e.g. volcanic ashes, particles, gas condensate) can deliver substantial amount of TSr and TLi to the water column. The distribution of TSr versus TLi evidences linear trends either with a negative or positive slope. The negative correlation is observed in the water column at both sites, directly under the influence of the eruption and in the vicinity of the volcano with hydrothermal activity. The positive TSr versus TLi correlation is observed at site under submarine hydrothermal influence and is in line with black smokers related hydrothermal plumes. The 87Sr/86Sr ratios vary between 0.709147 and 0.709210 and δ7Li values vary between +10.1 and +37.6 ‰. While 92% of the measured 87Sr/86Sr ratios are in line with the mean value of oligotrophic waters, once combined with the δ7Li values, only 20% of them remains within this field. The wide range of δ7Li values decreases from sea-surface down to ~140 mbsl, before increasing at greater depth, while defining different linear trend according to the dissolved inorganic carbon concentrations. The variability of δ7Li values reflect hydrothermal contribution, mineral–seawater interaction and potentially biology–environment interaction. In the particular geological setting of the study, where both hydrothermal and volcanic activities were at play, disentangling both contributions on water column implies a combined use of elemental and isotopic signatures of Sr and Li tracers.